Dialysis-related amyloidosis of the tongue - Israel, Monica Simoes; Pires, Fábio Ramôa; Freire, Nathalia Almeida; Sertorio, Bruno (Journal of Oral Diagnosis, 2019)
Background: As the aging process of the world population evolves, a progressive increase in the number of patients with kidney failure and consequently under long- term hemodialysis is expected. Dialysis-related amyloidosis, a disease characterized by deposits of β2-microglobulin, affects mainly the osteoarticular system, while involvement of the oral tissues is rare. Objective: We present an unusual case of lingual amyloidosis associated with hemodialysis in a 67-year-old male under dialysis for 24 years. Conclusion: It is important to understand the oral manifestations of systemic diseases for appropriate diagnosis and treatment of the affected patients.